Library and Internet: via Cable Network - a Propose - Mulla, K. R. (Journal of Information and Knowledge, 2014)
This article deals with the INTERNET. Miraculous developments in telecommunication systems and information technology have created marvels for the new generation i.e. Internet using a phone line. Internet via phone connections are painfully slow, especially when downloading photographs, graphics, or video images and large files. The cable modem technology for the Internet provides an ’always on’ feature for individuals to access the Internet rapidly, while its digital broadband network technology allows user to move around quickly.